Morning's gate - Roberts, Ann Victoria (New York : Morrow, 1991)
Sixty years after Liam Elliott's and Georgina Duncan's separation, Zoe Clifford, an Elliott descendant, and her cousin Stephen piece together the clues to their ancestor's love affair. By the author of Louisa Elliott. 100,000 first printing. $100,000 ad/promo.
Keywords: Detective and mystery stories; Great Britain -- History -- 20th century -- Fiction; Romantic suspense fiction